1997
DOI: 10.1002/(sici)1098-2345(1997)41:4<289::aid-ajp2>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Foraging ecology and use of space in wild golden lion tamarins (Leontopithecus rosalia)

Abstract: In this paper we describe the use of space and feeding ecology of seven groups of golden lion tamarins observed for a total of 2,164 hr in Poço das Antas Reserve, Rio de Janeiro, Brazil. Relative to habitat availability in the home ranges of these groups, lion tamarins spent more time than expected in relatively undisturbed swamp forests and less time than expected in more degraded hillside and pasture habitats. Home range area was correlated with group biomass but not group size. Golden lion tamarins fed prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(36 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Prey capture success in golden lion tamarins is highly variable (Miller and Dietz 2005), and foraging success rates vary 15–60% for adults, and are at 87% for juveniles in the 15 cases reported as putative teaching behavior (Dietz et al 1997; Peres 1989; Rapaport 2011; Rapaport and Ruiz-Miranda 2002). Compared to that in adults, the success rate observed in our experiment is slightly higher than those reported previously, which could be because the food we used could not escape the substrate (we used bananas instead of insects for logistical and ethical reasons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prey capture success in golden lion tamarins is highly variable (Miller and Dietz 2005), and foraging success rates vary 15–60% for adults, and are at 87% for juveniles in the 15 cases reported as putative teaching behavior (Dietz et al 1997; Peres 1989; Rapaport 2011; Rapaport and Ruiz-Miranda 2002). Compared to that in adults, the success rate observed in our experiment is slightly higher than those reported previously, which could be because the food we used could not escape the substrate (we used bananas instead of insects for logistical and ethical reasons).…”
Section: Discussionmentioning
confidence: 99%
“…They also have a broad diet, which includes fruits, flowers, nectar, exudates, bird eggs, fungi, insects, and small vertebrate prey (Dietz et al 1997; Lapenta et al 2003; Rylands 1989). Their food resources are patchily distributed over large home ranges, and are ephemeral (Dietz et al 1997). This creates the need for learning during ontogeny of what foods are good to eat, where to find them, and how to access them.…”
Section: Introductionmentioning
confidence: 99%
“…However, long, prehensile fingers in primates are also implicated in a greater ability to manipulate objects (Lemelin, ). Specialist manipulative foragers such as Leontopithecus have longer, narrower hands than other callitrichid genera (Bicca‐Marques, ), linked to their strategy of foraging in crevices such as bromeliads and tree holes (Dietz et al, ). The present study also found that Leontopithecus had significantly longer hands (and fingers) than Callithrix, Cebuella, Mico and Saguinus .…”
Section: Discussionmentioning
confidence: 99%
“…Where several studies had comparably collected/described data, average values were calculated. Data were collated from results in the following studies: Garber, 1 ; da Fonseca and Lacher, 2 ; Garber and Sussman, 3 ; Yoneda, 4 ,b; Garber, 5 ; Ayres and Clutton‐Brock, 6 ; Egler, 7 ; Ferrari and Strier, 8 ; Garber, 9 ; Peres, 10 ; Rosenberger, 11 ; Garber, 12 ; Peres, 13 ; Lopes and Ferrari, 14 ; Peres, 15 ; Garber and Pruetz, 16 ; Ferrari and Digby, 17 ; Dietz et al, 18 ; Peres, 19 ; Garber, 20 ; Hamrick, 21 ; Youlatos, 22 ; Araújo et al, 23 ; Corrêa et al, 24 ; Heymann and Buchanan‐Smith, 25 ; Heymann et al, 26 ; Martins and Setz, 27 ; Oliveira and Ferrari, 28 ; Garber and Leigh, 29 ; Miranda and Faria, 30 ; Porter, 31 ; Regan et al, 32 ; Lehman, 33 ; Porter, 34 ; Poveda and Sanchez‐Palomino, 35 ; Raboy and Dietz, 36 ; Bicca‐Marques, 37 ; Garber et al, 38 ; Yépez et al, 39 ; Cunha et al, 40 ; Burity et al, 41 ,; da Silva and Ferrari, 42 ; de Castro and Araújo, 43 ; Digby et al, 44 ; Garber, 45 ; Lapenta and Procópio‐de‐Oliveira, 46 ; Nadjafzadeh and Heymann, 47 ; Porter et al, 48 ; Raboy et al, 49 ; Garber et al, 50 ; Garber and Porter, 51 ; Porter et al, 52 ; Rehg, 53 ; Veracini, 54 ; Youlatos, 55 ; Hilário and Ferrari, 56 ; Porter and Garber, 57 ; Smith, …”
Section: Methodsmentioning
confidence: 99%
“…Lion tamarins ( Leontopithecus spp.) feed on a wide range of invertebrates and small vertebrates; by using their long fingers, they extract prey hidden in holes, crevices, beneath tree bark, and especially inside bromeliad plants (Dietz, Peres, & Pinder, ). Capuchin monkeys routinely exploit fruits with hard teguments, xylophagous insects and underground plant parts (Eadie, ; Fragaszy, Visalberghi, & Fedigan, ; O'Malley & Fedigan, ; Perry & Manson, ; Terborgh, ).…”
Section: Introductionmentioning
confidence: 99%